The impact of enterprise zones on the incubation and evolution of technology and manufacturing businesses in New York state - Hal Wesley Snarr; Dan Friesner (Review of Economic Analysis (REA), 2022)
The START-UP NY program is a creation-based entrepreneurial policy that sets up enterprise zones in several New York counties. The purpose of this study is to test the hypothesis that the program does not affect entrepreneurial activity in the industrial sectors it targets: manufacturing and high technology. Unlike many of the studies in the literature, which use indirect measures of entrepreneurial activity (e.g., unemployment rates, poverty rates, local economic growth, etc.), this analysis employs a direct measure-the number of firms that are targeted by the policy. Complicating the analysis is the state's subsequent tax reforms, which were implemented to promote creation- and discovery-based entrepreneurship in all parts of the state. To test our hypothesis, we control for this reform (and other factors) in a multiple equation difference-in-differences model. The results show that START-UP NY increases the number of 'micro' and 'small' firms in the targeted sectors by between 16.7% and 19.7% in the five years after the program was enacted.
Keywords: M13; O12; R11; J38; 330; entrepreneurship; employment; regional economic development